2011
DOI: 10.1021/jp202336j
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Topography: A Tool to Enhance Pore Order and Pore Size Distribution in Anodic Aluminum Oxide

Abstract: A. acknowledges the Faculty of Sciences of Oporto University for the financial support under the FCT project NANA/NMed-SD/ 0156/2007. J.V. and J.P.A. acknowledge financial support through FSE/POPH and Fundac -ão Gulbenkian ("Programa Gulbenkian de Estímulo a Investigac -ão Científica"), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 42 publications
2
43
0
3
Order By: Relevance
“…16 Prior to anodization, Al disks were cleaned in acetone and ethanol, and electropolished in a solution of 75% ethanol and 25% perchloric acid by applying 20 V for 2 min. 26 The subsequent anodization processes were performed in 0.3 M oxalic acid at 40 V, maintaining the electrolyte temperature at $4 C. To obtain ordered hexagonal nanopore arrays first anodizations were performed for 24 h. The alumina was then removed by chemical etching in an aqueous solution of 0.2 M H 2 CrO 4 and 0.4 M H 3 PO 4 at 60 C, and second anodizations were performed using the same conditions as the first ones, but only for $20 h, producing membranes with $ 50 lm in thickness. 22 The obtained NpATs had pore diameters of d $ 3564 nm and interpore distances of D int $ 10263 nm.…”
Section: Methodsmentioning
confidence: 99%
“…16 Prior to anodization, Al disks were cleaned in acetone and ethanol, and electropolished in a solution of 75% ethanol and 25% perchloric acid by applying 20 V for 2 min. 26 The subsequent anodization processes were performed in 0.3 M oxalic acid at 40 V, maintaining the electrolyte temperature at $4 C. To obtain ordered hexagonal nanopore arrays first anodizations were performed for 24 h. The alumina was then removed by chemical etching in an aqueous solution of 0.2 M H 2 CrO 4 and 0.4 M H 3 PO 4 at 60 C, and second anodizations were performed using the same conditions as the first ones, but only for $20 h, producing membranes with $ 50 lm in thickness. 22 The obtained NpATs had pore diameters of d $ 3564 nm and interpore distances of D int $ 10263 nm.…”
Section: Methodsmentioning
confidence: 99%
“…This shallow ripple-like structure is an EP characteristic of metals 40 and can be used as a pre-pattern prior to anodization to obtain highly ordered oxide nanostructures, as shown in the case of Al. 36,40,[42][43][44][45] The electrochemical polishing of Ti is usually achieved in sulphuric acid-based electrolytes, which results in smooth surfaces. 46 However, in this work the EP conditions used (electrolyte type and voltage) resulted in organized dimple patterns, 40 with an interripple spacial period = 97 nm [ Fig …”
Section: Ti Surface Topography Analysesmentioning
confidence: 99%
“…[25][26][27] On the other hand, the pre-treatment of the initial metal foil was shown to be a simple and efficient method to induce a high degree of organization in AAO templates. 36 In the TiO2 NT array case, studies using pretreatments such as electropolishing (EP) or mechanical polishing (MP) indicated that a Ti smooth surface is crucial to obtain highly ordered NT arrays since it ensures a uniform electric field distribution over the Ti surface during the anodization. [27][28][29]37 In particular, Lee et al showed that a decrease of the surface roughness by EP leads to NTs with a more uniform length and a higher density, but almost no hexagonal NT domains were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Each Al foil was rinsed in acetone, ethanol and distilled water. Immediately prior to anodization, the Al foils were individually electropolished in a stirred 10 °C bath of perchloric acid, HClO4, and ethanol, C2H5OH, (volume ratio 1 : 4) at 20 V during 2 min, to reduce surface roughness and create nanopatterns for posterior pore nucleation [28]. Finally, the substrates were rinsed in ethanol, followed by deionized water and dried in air.…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%